"THE RELATIONSHIP OF SOCIAL AND POLITICAL CONFLICTS AND THEIR SOLUTION" - Rakhmatov Otabek Odilovich (Galaxy International Interdisciplinary Research Journal, 2023)
In modern society, including domestic, the number of citizens who express dissatisfaction with the forms of political and social conflicts is growing. This article discusses the relationship between social and political conflicts and ways to resolve them.